Digital transformation in the legal sector: Challenges and opportunities for cybersecurity and data protection - Xhixho, Erisa; Pazylov, Niiazbek; Savchenko, Viktor; Patiev, Nurkhanbek; Pazylova, Munarym (Law, State and Telecommunications Review, 2025)
[Purpose] The purpose of this study was to examine the principal issues of cybersecurity and data protection in the context of digital transformation in the legal system of the Kyrgyz Republic. [Methodology/approach/design] The study conducted legal and comparative analysis of the regulatory framework and its application in modern conditions. Additionally, the content of reports from governmental and international organisations was examined to assess current trends in data protection and digital services. The study analysed key documents such as the National Development Strategy of the Kyrgyz Republic for 2018-2040 and the Concept of Digital Transformation of the Kyrgyz Republic for 2024-2028, the Civil and Criminal Codes of the Kyrgyz Republic, as well as laws of the Kyrgyz Republic regulating access to information, data protection, and cybersecurity, namely, “On the Right of Access to Information”, “On Protection of State Secrets of the Kyrgyz Republic”, “On the National Archive Fund of the Kyrgyz Republic”, “On the Electrical Connection”. Special attention was paid to the Tunduk system as an essential element of digital public administration and interaction between public authorities. [Findings] The key findings showed that despite great strides in digitalisation, the existing legislative framework of the Kyrgyz Republic needs considerable adaptation to ensure data protection and cybersecurity in a rapidly evolving digital environment. [Practical implications] The study offered recommendations, including the creation of a national cybersecurity centre, the introduction of international data protection standards, and the development of human resources in the field of information security. [Originality/value] The findings confirm the need to modernise the legal framework to ensure a sustainable and secure digital transformation in the Kyrgyz Republic, which is critical for protecting citizens’ data and increasing trust in public services.